2012
DOI: 10.3390/ijms13067663
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Sox2 and Oct4 and Their Clinical Significance in Human Non-Small-Cell Lung Cancer

Abstract: Sox2 and Oct4 are transcription factors with the characteristics of regulating self-renewal and differentiation of embryonic stem cell. The aim of this study was to detect the expression of Sox2 and Oct4 and analyze their clinical significance in human non-small-cell lung cancer (NSCLC). Expression of Sox2 and Oct4 were assayed in cancer tissues and their corresponding paracancerous tissues from 44 patients with NSCLC and 21 patients with benign tumors using immunohistochemistry, Western blot, reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 36 publications
6
66
1
1
Order By: Relevance
“…Discussion SOX2 is a highly recurrent amplified oncogene in multiple forms of SCC and has been implicated in breast and prostate carcinomas and glioblastoma (12)(13)(14). Many have hypothesized that SOX2 and OCT4 act coordinately in cancer to induce "stem-like" tumors that are poorly differentiated and demonstrate poor survival (36)(37)(38). In SCCs, in contrast, SOX2 amplification is largely a positive prognostic marker (2,15).…”
Section: Figurementioning
confidence: 99%
“…Discussion SOX2 is a highly recurrent amplified oncogene in multiple forms of SCC and has been implicated in breast and prostate carcinomas and glioblastoma (12)(13)(14). Many have hypothesized that SOX2 and OCT4 act coordinately in cancer to induce "stem-like" tumors that are poorly differentiated and demonstrate poor survival (36)(37)(38). In SCCs, in contrast, SOX2 amplification is largely a positive prognostic marker (2,15).…”
Section: Figurementioning
confidence: 99%
“…SOX2 has been found in brain, breast, lung, liver, prostate, and testicular tumors [12, 18, 19]; and its expression has been correlated with poor prognosis in stage I lung adenocarcinoma [18], squamous cell carcinoma [20, 21], gastric carcinoma [22-24], small cell lung cancer [25-28], and ovarian carcinoma [29, 30]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently it was revealed that new stem cell markers emerged while studying the process of tumour initiation and progression [27]. The present study was carried out with a well-documented stemness associated marker named Sox2 [23].…”
Section: Discussionmentioning
confidence: 99%